El primerWalsh: el género policial como laboratorio - Paletta, Viviana (Anales de Literatura Hispanoamericana, 2008)
This study analyzes the Rodolfo Walsh’s first detective short stories published in the newspapers (1950-1964), and not included in Variaciones en rojo (1953). The study takes special attention to the two «Las tres noches de Isaías Bloom» versions (1950 and 1954). Those stories are characterized by his hesitations in the genre and by his adaptation to the local context. Also, it is possible to see his future poetics typical features: his worry to register the colloquial way of speaking, the inclusion of the Argentinean landscape and his social restlessness.